Challenges of Transition Faced by Freshman Students: An Academic Study - Sofa Priyandayani Nasution; Donny Adiatmana Ginting; Srimaharani Tanjung (PROJECT (Professional Journal of English Education), 2026)
The transition from senior high school to university often requires significant academic adaptation, particularly for students entering English Literature programs where learning approaches differ substantially from secondary education. This study examines the varied challenges faced by first-year English Literature students at Bangka Belitung University as they adapt to the shift from structured high school language learning to university-level study that emphasizes critical interpretation, literary theory, etc. Using a mixed-methods design involving 72 survey respondents and 5 interview participants, the study examines six domains of academic adaptation: teaching methods, course content, evaluative methods, psychological and educational support, academic environment, and learning conditions. Quantitative findings indicate that teaching methods constitute the most dominant challenge (M = 3.79), followed by course content and learning conditions (M = 3.55). Qualitative findings reveal that adaptation is not linear but interconnected, involving identity reconstruction, emotional regulation, and self-regulated learning development. The study addresses a research gap by bringing university system and individual experiences in learning English in an Indonesian university context. The results suggest the pedagogical reforms, structured orientation programs, and supportive assessment practices to help English Literature Students navigate their transition into university students.